For this case we have that by definition, the equation of a line in the slope-intersection form is given by:
Where:
m: Is the slope
b: Is the cut-off point with the y axis
According to the data of the statement we have to:
[tex]m = 1[/tex]
Then, the equation is of the form:
[tex]y = x + b[/tex]
We substitute the point [tex](1, -5)[/tex] and find "b":
[tex]-5 = 1 + b\\-5-1 =b\\-6 = b[/tex]
Thus, the equation is of the form:
[tex]y = x-6[/tex]
To graph we substitute the points on the coordinate axis:
[tex](x, y) :( 0, -6)[/tex]
For [tex]x = 2[/tex]:[tex]y = 2-6 = -4[/tex] [tex](2, -4)[/tex]
For [tex]x = 10[/tex]: [tex]y = 10-6 = 4[/tex] [tex](10,4)[/tex]
Answer:
[tex]y = x-6[/tex]
See attached image